Expansion of Neutrophils and Classical and Nonclassical Monocytes as a Hallmark in Relapsing-Remitting Multiple Sclerosis - Haschka, David; Tymoszuk, Piotr; Bsteh, Gabriel; Petzer, Verena; Berek, Klaus; Theurl, Igor; Berger, Thomas; Weiss, Günter (Frontiers in Immunology, 2020)
Neutrophils and monocytes encompassing the classical, intermediate and non-classical population constitute the majority of circulating myeloid cells in humans and represent the first line of innate immune defense. As such, changes in their relative and absolute amounts serve as sensitive markers of diverse inflammatory conditions. Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system causing demyelination and axonal loss affecting various neuron functions and often causing irreversible neurological disability. MS disease course is individually highly heterogenous but can be classified as progressive (PMS) or relapsing-remitting (RRMS). Each MS course type may be further characterized as active or inactive, depending on the recent disability progression and/or current relapses. Data on specific alterations of the myeloid compartment in association with MS disease course is scarce and conflicting. In the current study, we systematically immunophenotyped blood myeloid leukocytes by flow cytometry in 15 healthy and 74 MS subjects. We found a highly significant expansion of neutrophils, classical and non-classical monocytes in inactive RRMS (RRMSi), which did not correlate with biochemical readouts of systemic inflammation. Each of these leukocyte populations and the combined myeloid signature accurately differentiated RRMSi from other MS forms. Additionally, non-classical monocyte proportions were particularly elevated in RRMSi individuals receiving disease-modifying therapy (DMT), such as natalizumab. Our results suggest that flow cytometry-based myeloid cell immunophenotyping in MS may help to identify RRMSi earlier and facilitate monitoring of DMT response.